English Translation Of The Meaning Of AL-QURAN : The Guidance for Mankind - Muhammad Farooq i Azam Malik (DAR Al wahi publication, 2015)
The subline quran, revealed through the blessed prophet muhammad in the early seventh century continues to inspire the belivers eith its majestic and wisdom, while its intrinsic beauty and level of meaning have remained an awesome challenge to would be translators